Measuring selected parameters of polypropylene fibre heat exchangers - Čarnogurská, Mária (Strojniški vestnik, 2016)
Heat exchangers whose heat exchange surfaces are made of the miniature polypropylene fibres are still under development. In the first phase of researching such exchangers, the possibility of attaching fibres into bundles was tested. The number of threads in one bundle ranges from several hundred to thousands of pieces. The sensitive element in the application of the fibres in a heat exchanger is the place where all the fibres are bundled together, into so-called potting, which must be perfectly tight. Pressure loss was measured in such bundles, depending on the water flow and the temperature at the entry and exit of the exchanger. The results allowed the definition of the overall heat transfer coefficient from one medium through the fibre wall to the other media and to determine the thermal performance of the exchanger. Experimental data shows that water-to-water heat exchanger reached the overall heat transfer coefficient value of to 800 W%m -2 %K -1 , depending on the release rate of the bundle. Subsequently, for the given conditions, the heat transfer rate depends only on the size of the heat transfer surface area, thus the number of fibres in the bundle.
Keywords: celotni koeficient prenosa toplote; meritev; polipropilenska vlakna; prenosnik toplote